2024
DOI: 10.1001/jamaophthalmol.2023.6917
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Large Language Model’s Responses to Questions and Cases About Glaucoma and Retina Management

Andy S. Huang,
Kyle Hirabayashi,
Laura Barna
et al.

Abstract: ImportanceLarge language models (LLMs) are revolutionizing medical diagnosis and treatment, offering unprecedented accuracy and ease surpassing conventional search engines. Their integration into medical assistance programs will become pivotal for ophthalmologists as an adjunct for practicing evidence-based medicine. Therefore, the diagnostic and treatment accuracy of LLM-generated responses compared with fellowship-trained ophthalmologists can help assess their accuracy and validate their potential utility in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 13 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…One possible explanation is that uniqueness neglect—a concern that algorithm providers are less able than human providers to account for residents’ (or patients’) unique characteristics and circumstances—drives consumer resistance to digital medical technology [ 23 ]. Therefore, personalized health management solutions based on large language models should be developed urgently [ 24 ] to meet the residents’ individual demands. In addition, a survey of population preferences for medical AI indicated that the most important factor for the public is that physicians are ultimately responsible for diagnosis and treatment planning [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that uniqueness neglect—a concern that algorithm providers are less able than human providers to account for residents’ (or patients’) unique characteristics and circumstances—drives consumer resistance to digital medical technology [ 23 ]. Therefore, personalized health management solutions based on large language models should be developed urgently [ 24 ] to meet the residents’ individual demands. In addition, a survey of population preferences for medical AI indicated that the most important factor for the public is that physicians are ultimately responsible for diagnosis and treatment planning [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, ChatGPT-3.5 had similar or better accuracy than senior ophthalmology residents in diagnosing primary and secondary glaucoma cases retrieved from a public online database [ 7 ]. Similarly, ChatGPT-4 outperformed glaucoma specialists and was comparable with retina specialists in diagnostic and treatment accuracy of glaucoma and retina cases [ 8 ]. By contrast, ChatGPT exhibited reasonable but inferior diagnostic accuracy than human experts in cornea [ 9 ], uveitis [ 10 , 11 ], and neuro-ophthalmology [ 12 ] cases.…”
Section: Discussionmentioning
confidence: 99%